IMPLEMENTASI HAK ANGKET DEWAN PERWAKILAN RAKYAT DALAM MELAKUKAN KONTROL ATAS KEBIJAKAN PEMERINTAH - Daniel Panggabean (Nommensen Journal of Legal Opinion, 2022)
The Inquiry rights is the right of the DPR to conduct an investigation into the implementation of a government law and/or policy relating to important, strategic, and broad impact on community, national, and state life that is suspected to be contrary to laws and regulations. The DPR's inquiry rights relating to the implementation of the DPR oversight function are “an institutionalized system, involving the effectiveness and regularity of restrictions on government actions. In Indonesian constitutional practice, the right of questionnaire is rarely implemented. Twice carried out during the reign of the old order and twice during the reign of the new order. The use of questionnaire rights in the current presidential system shows a significant increase. This research uses normative juridical methods that are descriptive analytical. Basically, the right of inquiry is a constitutional right of the House of Representatives in the constitutional system of the Republic of Indonesia as part of carrying out the function of supervision and balance over the executive. As a result of the law of application of the right of questionnaire, the House of Representatives can exercise the right to express opinions.